Assessing the Role of Information Technology in Promoting Sustainable and Renewable Energy in Helambu Rural Municipality, Nepal - Mahate, Samaya (NPRC Journal of Multidisciplinary Research, 2025)
The study examines the role of Information Technology (IT) in Kutumsang village, Helambu Rural Municipality, in terms of energy problems, access, and affordability. The research methodology employed for this study was the combination of primary and secondary data collection methods. Primary data collection methods were a Key Informant Interview (KII) session with the elected head of the Helambu Rural Municipality and a Q/A session with the local people of Ward 7 in Kutumsang village. The results show that hydropower is the primary energy source, while the use of the solar energy is very limited and there has been a decline in biogas systems due to climate factors; however, diesel and gasoline are still demanded for transport. The study suggests that lack of institutional support, high prices, and unreliable supply are the major issues faced by the community. One significant outcome of the research is the identification of a very limited role for IT in the local energy management systems even though it has the potential to greatly assist in planning, monitoring, and service delivery. The findings suggest that IT-based tools such as digital data systems, GIS-supported spatial planning, smart monitoring, and mobile-based reporting could bring about substantial improvements in energy governance, transparency, and operational efficiency. The researchers, therefore, point out that the combination of renewable energy with IT-enabled systems can improve local sustainability, reliability and also the quality of decisions made. The study adds to the existing literature on the rural energy assessment from an IT perspective providing a context-specific framework for IT-supported sustainable energy development in Nepal as its main contribution.